MODEL PENGUATAN EKSISTENSI LAZNAS YATIM MANDIRI DALAM STRATEGI PENINGKATAN DONASI - Rosyidah, Norma (Universitas Negeri Surabaya, 2026)
The existence of LAZNAS Yatim Mandiri as a non-profit social institution can be seen from the increase in donations, which then create empowerment programs for people in need. The research aims to determine and analyze the factors influencing the increase in LAZNAS Yatim Mandiri donations. This research used a quantitative approach, with 215 Zakat Consultants (ZISCO) Yatim Mandiri respondents. The data collection method used was a survey by distributing questionnaires. Data was tested using the PLS-SEM via SmartPLS 3.0. The test results indicate that social awareness directly influences increasing donations, and the institution's image through social marketing campaigns significantly influences increasing donations. The institutional image variable, which the technology acceptance model strengthens, the institutional transparency variable, and the social marketing campaign, strengthened by financial te, significantly influence increasing donations. Research testing at LAZNAS Yatim Mandiri is the first and is something new to determine what factors influence the increase in LAZNAS Yatim Mandiri donations in the current era.